Media and Psychological Polarization of Society: a Systematic Review of Interdisciplinary Foreign Research - A.V. Vanin; O.V. Gordyakova; A.N. Lebedev (Современная зарубежная психология)
The paper analyzes foreign studies of the relationship of modern media with various characteristics of the psychological polarization of social groups. The research method was a systematic review of the literature conducted on 187 relevant scientific publications covering the time period from 1990 to 2023. In the course of the work, the connection between traditional media and the Internet was described on the issues of studying the phenomenon of psychological polarization at the qualitative and quantitative levels. Three main chronological and thematic stages of the study of the problem were identified; The geographical and disciplinary affiliation of the authors of the research is established; the key concepts characterizing the subject of research are analyzed; theories and mechanisms explaining the phenomenon of polarization are presented. As a result of the study, it was shown: 1) the quantitative predominance in the literature of research results confirming the hypothesis of the connection of media with various aspects of polarization; 2) the revealed connection is characterized by the significant role of traditional media, the Internet and social networks in increasing polarization in society, rather than in their hypothetically possible depolarizing effect.